Empfehlungen zur extrakorporalen kardiopulmonalen Reanimation (eCPR): Konsensuspapier der DGIIN, DGK, DGTHG, DGfK, DGNI, DGAI, DIVI und GRC - Michels, Guido; Preusch, Michael (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2018)
Extracorporeal cardiopulmonary resuscitation (eCPR) may be considered as a rescue attempt for highly selected patients with refractory cardiac arrest and potentially reversible etiology. Currently there are no randomized, controlled studies on eCPR, and valid predictors of benefit and outcome which might guide the indication for eCPR are lacking. Currently selection criteria and procedures differ across hospitals and standardized algorithms are lacking. Based on expert opinion, the present consensus statement provides a proposal for a standardized treatment algorithm for eCPR.
Gesehen am 10.07.2019